1992
DOI: 10.1017/s0144686x00005262
|View full text |Cite
|
Sign up to set email alerts
|

The Construction and Deconstruction of Self in Alzheimer's Disease

Abstract: The loss of self in Aizeheimer's Disease is examined from a social constructionist view of the nature of the self. Empirical evidence derived from the structure of the discourse and behaviour of three Alzheimer's sufferers is presented to show that self1, the self of personal identity, persists far into the end stage of the disease. Self2, the multiple personae that are projected into the public arena, and which require the cooperation of others in order to come into being, can be lost, but only indirectly as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
334
1
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 450 publications
(352 citation statements)
references
References 8 publications
10
334
1
3
Order By: Relevance
“…Whereas dementia research often focuses on self-esteem as an internally derived form of self-conception, which becomes susceptible to the invasive effects of the illness (eg, Brod et al, 1999), of course social relations influence our social esteem (Honneth, 1995). Accordingly, a decline of self in dementia may result from the loss of recognition by others (Sabat and Harre, 1992). The sense of 'ontological insecurity' evident among some of the people with dementia in the study indicated that, while their understanding of their social lives was reduced, they were still conscious of subtle changes in relationship dynamics.…”
Section: Using Emotion As a Moral Guide To Social Lifementioning
confidence: 92%
“…Whereas dementia research often focuses on self-esteem as an internally derived form of self-conception, which becomes susceptible to the invasive effects of the illness (eg, Brod et al, 1999), of course social relations influence our social esteem (Honneth, 1995). Accordingly, a decline of self in dementia may result from the loss of recognition by others (Sabat and Harre, 1992). The sense of 'ontological insecurity' evident among some of the people with dementia in the study indicated that, while their understanding of their social lives was reduced, they were still conscious of subtle changes in relationship dynamics.…”
Section: Using Emotion As a Moral Guide To Social Lifementioning
confidence: 92%
“…Self-identity is changed-not totally lost-and typically is preserved into the end stage of advanced dementia (Harris & Sterin, 1999;Sabat & Harré, 1992). The consequence of this changing self-identity is a new form of life, a new way of living in the world that is fraught with incoherence and unknown meaning.…”
Section: The Changing Self and Public Identitymentioning
confidence: 99%
“…Sabat (Sabat 2002;Sabat and Harre 1992) adapted Goffman's theory to dementia, with a distinction between three different aspects -Self 1, Self 2, and Self 3. Self 1 is the internal sense of identity, how we keep a record of our autobiography.…”
Section: Theoretical Perspectives On the Self And Identitymentioning
confidence: 99%